A docência no ensino técnico integrado ao ensino médio durante o ensino remoto: as significações de professores de um campus do IFSP - Bayer, Julia Sotto-Maior (2021)
This study intended to explain and analyze the meanings of teaching in technical education integrated to high school, during remote teaching, based on Socio-Historical Psychology and Historical-Dialectical Materialism. Given the centennial history of the Federal Network of Professional and Technological Education and the proposition of Integrated High School, developed in the Federal Institutes of Education, Science and Technology, one wondered about the constitutive movements of the teachers' meanings concerning their practice in one new campus of the IFSP. Regarding the devaluation of teacher education in the history of the network. The structural duality established in Brazilian education and the characteristics of the traditionally professional training offered in the professional education institutions comprised the teaching work development context of the technical education integrated to high school. The implementing process of the emergency organized remote teaching in the IFSP, with the COVID-19 pandemic, was incorporated as a constitutive mediation of the teaching social totality. Six teachers in technical education integrated to high school participated, two from professional education subjects, and four from general education subjects. The reflective interviews and the conversations inspired the interview methodology, and the information was articulated in two nuclei, carried out by the analysis procedure of the Nuclei of Meaning. The Nuclei 1 - "I think that other campuses, which grew with all these changes, understood the reason for these changes": between the institutional culture and the new educational proposals in the process of expansion of the Federal Network of TPE. The Nuclei 2 - "[...] our educational quality was not what we would like, before the pandemic, for several reasons, with the pandemic, it is going to get worse, for sure, you know?": The reflective movements of teachers about their conditions and their work during remote education. The analytical process evidenced that the culture established in the country's history of technician education constituted teachers' meanings and tensioned the new possibilities presented to teaching by the institutional transformation into federal institutes. These references appeared in our participants' meanings, presented in several ways: by notes of continuity or rupture in the teaching trajectory, by the presentation of emphasis on technical education on campus or the accentuation on high school, by the complaint of lesser space for human formation, by the desire to promote a critical and integrated education and by the dispute about the possible activities on teaching in the IFSP. The emergency organization of remote education has highlighted a pedagogical crisis in the institution, which is part of a conjuncture crisis. Within the institution, the integration, based on interdisciplinarity, was highlighted as the basis to constitute possible activities, to tension politically the orientation of education offered to young people